2014
DOI: 10.33762/bvetr.2014.88143
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Salmonella Spp. From Poultry Farms by Using Different Techniques and Evaluation of Their Antimicrobial Susceptibilities

Abstract: This study aimed to isolate and identify Salmonella spp. from various sources of poultry farms by using four different techniques (conventional biochemical tests, API 20E system, serology and polymerase chain reaction) the total number of isolates was 44(9%). The Salmonellae including 4 species, S. gallinarum 9(1.85%), S. typhimurium 7(1.44%), S. newport 21(4.3%) and S. ohio 1(0.21%). The highest isolation rate was in first week of chicks life 18(25.7%), however, the highest isolation rate of salmonella was fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
3
3
0
Order By: Relevance
“…The prevalence of the isolated bacteria from different internal organs of the examined layers in this study showed that the highest percentage of Salmonella was recorded in liver (37.5%) followed by cecum (33,3%), ovary (20.8%) and heart (8.3%). These results are in agreement with Dhahar et al [22] and AL-Iedani [23]. AL-Abadi and Al-Mayah [20] recorded that the highest percentage of Salmonella isolation was from cecum which is the primary sites of colonization of Salmonella due to the anatomical and structural location that allows the cecum to act as a blind sac with low content flow rate.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of the isolated bacteria from different internal organs of the examined layers in this study showed that the highest percentage of Salmonella was recorded in liver (37.5%) followed by cecum (33,3%), ovary (20.8%) and heart (8.3%). These results are in agreement with Dhahar et al [22] and AL-Iedani [23]. AL-Abadi and Al-Mayah [20] recorded that the highest percentage of Salmonella isolation was from cecum which is the primary sites of colonization of Salmonella due to the anatomical and structural location that allows the cecum to act as a blind sac with low content flow rate.…”
Section: Discussionsupporting
confidence: 90%
“…Also a same study was carried out by Desai et al (2005) for the serotype-specific detection of Pullorum and its differentiation from the closely related Gallinarum using a rapid allele-specific polymerase chain reaction (PCR) method based on the nucleotide polymorphism in rfbS gene sequence. This observation also confirms the preliminary findings made by Park et al (2001) in Korea for differential diagnosis of S. Gallinarum and S. Pullorum using PCR-RFLP and AL-Iedani et al (2014) using rfbsg and rfbsp genes amplification of S. gallinarum and S. pullorum . Salmonella possess surface structures that can induce protective humoral and cellular immune responses following experimental infection in poultry (Liu et al, 2001;Timms et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…They are inexpensive antibiotics, which have been used extensively in the prophylaxis and therapy of human and animal infections and also at subtherapeutic levels in animal feed as growth promoters. [42], in the present study chicken showing high resistance to be recorded against Tetracycline, [43,44]. Higher rates of resistance were observed to extend spectrum penicillin, these antimicrobial resistances of Salmonella spp.…”
Section: Discussionsupporting
confidence: 50%